2021
DOI: 10.3390/s21030969
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hospital Mortality in Patients with Acute Coronary Syndrome Complicated by Cardiogenic Shock

Abstract: As demonstrated by earlier studies, pre-hospital triage with trans-telephonic electrocardiogram (TTECG) and direct referral for catheter therapy shows great value in the management of out-of-hospital chest pain emergencies. It does not only improve in-hospital mortality in ST-segment elevation myocardial infarction, but it has also been identified as an independent predictor of higher in-hospital survival rate. Since TTECG-facilitated triage shortens both transport time and percutaneous coronary intervention (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…A previous study indicated that an extended interval between symptom onset and hospitalization was the most important independent predictor of an increased risk of in-hospital mortality [21].However, in this study, the symptom onset to ED arrival time, symptom onset to PCI initiation time, categorized time interval from symptom onset to initiation of PCI (≥720 or <720), and the time interval from the ED visit to the initiation of PCI (<30 min, ≥30 min,<60 min, and ≥60 min) did not differ between the No-SHDG and SHDG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study indicated that an extended interval between symptom onset and hospitalization was the most important independent predictor of an increased risk of in-hospital mortality [21].However, in this study, the symptom onset to ED arrival time, symptom onset to PCI initiation time, categorized time interval from symptom onset to initiation of PCI (≥720 or <720), and the time interval from the ED visit to the initiation of PCI (<30 min, ≥30 min,<60 min, and ≥60 min) did not differ between the No-SHDG and SHDG.…”
Section: Discussionmentioning
confidence: 99%
“…These results show a tendency for an overall positive correlation between RECS implementation and SHD prediction. A recent study showed that telehealth increased the fatality rate by 13.7% in the non-treated group, compared to 4.1% in an administered group of patients with STEMI during the COVID-19 pandemic [21]. Another study reported that pre-hospital triage with a trans-telephonic electrocardiogram and direct referrals for catheter therapy were independent predictors for improved in-hospital survival and mortality in patients with STEMI [22].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of blood-derived biomarkers in risk stratification patients with AMI-related CS may be of major importance since the identification of appropriate risk prediction tools following AMI-related CS remains challenging. Good myocardial reperfusion following PCI and renal function, assessed with glomerular filtration rate (GFR), was recently demonstrated to improve outcomes in AMI-related CS patients [ 33 ]. The prognostic value of the renal function in CS was verified within a sub-study of the CULPRIT-SHOCK study [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these factors account for the worse long-term prognosis of diabetic patients presenting with STEMI. On the other hand, DM was not identified as an independent predictor of in-hospital mortality in patients with acute coronary syndrome complicated by cardiogenic shock [ 39 ]. More aggressive pharmacotherapy might mitigate these detrimental effects of DM [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%